Engaging psychologically or behaviourally? A segmentation of the integrated resort customers - Carl Cater (Tourism Management Perspectives, 2024)
Academic studies that highlight the importance of customer engagement for sustaining organisational success have generally assumed that engaged customers are a homogenous market segment. This study provides an alternative scholarly perspective by reconsidering the multidimensionality of customer engagement and uses cognitive, affective, and behavioural elements to segment customers. A cluster analysis with data from 574 integrated resort customers in Macau, China supports the three-dimensional structure, and additional analyses show that customers can be segmented into totally-engaged, shallowly-engaged, potentially-engaged, and non-engaged groups based on their psychological investment (which consists of cognitive and affective engagements) and behavioural engagement. The findings both address the dimensional structure of customer engagement in the market segmentation context and provide some valuable theoretical and market segment-related managerial implications.